2018
DOI: 10.3390/plants7010009
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilizer Management in Dryland Wheat Cropping Systems

Abstract: Wheat is the most widely cultivated food crop in the world, which provides nutrition to most of the world population and is well adapted to a wide range of environmental conditions. Timely and efficient rates of nitrogen (N) application are vital for increasing wheat grain yield and protein content, and maintaining environmental sustainability. The goal of this study was to investigate the effect of using different rates and split application of N on the performance of spring wheat in dryland cropping systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 19 publications
6
40
0
1
Order By: Relevance
“…The effects of split‐applying N showed relatively modest increases in grain yield and protein content in this study. These results are comparable to Walsh et al (2018), who found little effect from split‐applying N on spring wheat in a similar climate in Montana. However, previous research has shown that late‐season N applications can result in higher protein content, which is supported by Treatment 7 of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…The effects of split‐applying N showed relatively modest increases in grain yield and protein content in this study. These results are comparable to Walsh et al (2018), who found little effect from split‐applying N on spring wheat in a similar climate in Montana. However, previous research has shown that late‐season N applications can result in higher protein content, which is supported by Treatment 7 of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…Zhang et al [44] indicated that discrepancies in the optimal N dose and maximum yield may have resulted from environmental variability. Walsh et al [45] did not find any significant differences in wheat grain yield under two levels of N fertilization: 90 and 135 kg N ha −1 . Haile et al [46] reported that different rates of N fertilization significantly increased wheat grain yield, and its maximum was achieved by application of 120 kg N ha −1 (however, optimal yield was not achieved as the response apparently did not plateau out).…”
Section: Resultsmentioning
confidence: 87%
“…The grain yield generally increases with the increase in nitrogen application within a certain range. However, the grain yield neither significantly increased nor decreased when the nitrogen fertilizer was applied outside a certain range . The experiments from three nitrogen levels (0, 120, and 240 kg ha −1 ) showed that wheat yield and nitrogen fertilizer absorption efficiency were significantly increased at 240 kg ha −1 .…”
Section: Discussionmentioning
confidence: 96%
“…However, the grain yield neither significantly increased nor decreased when the nitrogen fertilizer was applied outside a certain range. 47 The experiments from three nitrogen levels (0, 120, and 240 kg ha −1 ) showed that wheat yield and nitrogen fertilizer absorption efficiency were significantly increased at 240 kg ha −1 . 48 Our recent studies have also indicated that the application of 240 kg ha −1 nitrogen significantly promoted the thousand-grain weight, grain yield, protein content, dough strength, and breadmaking quality when compared with 180 kg ha −1 .…”
Section: Influence Of Different N Fertilizer Applications On Cfwn Andmentioning
confidence: 97%